Effects of Core Stabilization Exercises on Pulmonary Function, Respiratory Muscle Strength, Peripheral Muscle Strength, Functional Capacity, and Perceived Appearance in Children With Adolescent Idiopathic Scoliosis: A Randomized Controlled Trial - YILDIRIM, SEFA; Yıldırım, Sefa; ÖZYILMAZ, SEMIRAMIS; Özyılmaz, Semiramis; ELMADAĞ, NUH MEHMET; Elmadağ, Nuh Mehmet; YABACI TAK, AYŞEGÜL; Yabacı Tak, Ayşegül (My University, 2022)
ObjectiveThe aim of the study was to investigate the effects of core stabilization exercises on pulmonary function, respiratory muscle strength, peripheral muscle strength, walking capacity, andperceived appearancein children with adolescent idiopathic scoliosis.DesignThis is an evaluator-blinded, randomized controlled trial. A total of 30 patients were randomly allocated to either a training group (n= 15, age = 13.8 ± 2.8 yrs, Cobb angle = 19.3 ± 6 degrees, Risser sign:n(1)= 1;n(2–4)= 14) or a control group (n= 15, age = 15.8 ± 3.4 yrs, Cobb angle = 20.8 ± 7.9 degrees, Risser sign:n(1)= 1;n(2–4)= 14). The training group received core stabilization exercises in addition to the traditional scoliosis exercises for 8 wks. The control group only received the traditional scoliosis exercises for 8 wks. Spirometry, maximal inspiratory and expiratory pressures, 6-min walking test, peripheral muscle strength, and the Walter Reed Visual Assessment Scale were assessed at the beginning and end of the study.ResultsThe training group showed statistically significant improvements in maximal inspiratory pressure, maximum expiratory pressure, and Walter Reed Visual Assessment Scale score (respectively, mean changes = 17.4 ± 5.2 cmH2O; 10.6 ± 4.3 cmH2O; 2.4 ± 1.6), which were significantly larger compared with the control group (P< 0.05).ConclusionsCore stabilization exercises given in addition to the traditional scoliosis exercise can improve respiratory muscle strength andperceived appearancein patients with adolescent idiopathic scoliosis.